The complete DNA sequence of lymphocystis disease virus - Tidona, Christian; Darai, Gholamreza (Virology, 1997)
Lymphocystis disease virus (LCDV) is the causative agent of lymphocystis disease, which has been reported to occur in over 100 different fish species worldwide. LCDV is a member of the familyIridoviridaeand the type species of the genus Lymphocystivirus. The virions contain a single linear double-stranded DNA molecule, which is circularly permuted, terminally redundant, and heavily methylated at cytosines in CpG sequences. The complete nucleotide sequence of LCDV-1 (flounder isolate) was determined by automated cycle sequencing and primer walking. The genome of LCDV-1 is 102.653 bp in length and contains 195 open reading frames with coding capacities ranging from 40 to 1199 amino acids. Computer-assisted analyses of the deduced amino acid sequences led to the identification of several putative gene products with significant homologies to entries in protein data banks, such as the two major subunits of the viral DNA-dependent RNA polymerase, DNA polymerase, several protein kinases, two subunits of the ribonucleoside diphosphate reductase, DNA methyltransferase, the viral major capsid protein, insulin-like growth factor, and tumor necrosis factor receptor homolog.
Elektronische Reproduktion der Druck-Ausgabe 25. Mai 2002
Gesehen am 29.08.2024